PENGARUH KARAKTERISTIK MANAJERIAL TERHADAP INTENSI TURNOVER KARYAWAN DAN KINERJA INDUSTRI KECIL KERIPIK SANJAI DI KOTA BUKITTINGGI - Yenni Del Rosa - (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2015)
This study was conducted based on the phenomena of managerial characteristics, turnover intention and small industrial performance chips Sanjai in Bukittinggi, therefore this research aims to know: First influences managerial characteristics on turnover intention. Both managerial influence on the performance characteristics of small industry. The third influence turnover intentions on the performance of small industries. The study was conducted using a survey with explanatory type. The study population was 25 chips Sanjai owners of small industries in the city of Bukittinggi where samples were taken by total sampling. The data used in the form of primary and secondary data. The research variables are grouped into observed variables and latent variables were collected using a Likert scale of 1 - 5. For the analysis of the data used Structural Equation Modeling (SEM). Research intention variables based on hypothesis testing showed that: First managerial characteristics significantly influence turnover intentions (p = 0.026 < 0.05). Both managerial characteristics no significant effect on the performance of small scale industries (p = 0.456 > 0.05). Third turnover intentions affect the performance of small scale industries (p = 0.002 < 0.05).Keywords:managerial characteristics, turnover intention, small industrial performance